1975
DOI: 10.1190/1.1440538
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization‐inclination Estimation From Prism‐like Anomaly Profiles

Abstract: Magnetization inclination in a two‐dimensional source body that produces a prism‐like magnetic anomaly, i.e., an anomaly that appears to be due to a two‐dimensional, rectangular prism, can be estimated by solving the nonlinear inverse problem of a horizontal equivalent‐source layer with unknown magnetization‐amplitude distribution and magnetization inclination. The equivalent source layer is chosen to be symmetric about the anomaly’s degree‐of‐symmetry point, determined by the method of Lamontagne, and the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1979
1979
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…If remanent effects can be identified, several approaches can be used to determine the magnetization parameters (Hall, 1959;Bhattacharyya, 1966;Bott et al, 1966;Cordell and Taylor, 1971;Emilia and Massey, 1975;Shurbet et al, 1976;Schnetzler and Taylor, 1984;Muniruzzaman and Banks, 1989), many of which require restrictive assumptions about the geometry or the gravity field of the sources. Most often, forward modeling is the only way, absenting extensive sampling, to obtain an estimate of magnetization parameters which are, however, not unique.…”
Section: Introductionmentioning
confidence: 99%
“…If remanent effects can be identified, several approaches can be used to determine the magnetization parameters (Hall, 1959;Bhattacharyya, 1966;Bott et al, 1966;Cordell and Taylor, 1971;Emilia and Massey, 1975;Shurbet et al, 1976;Schnetzler and Taylor, 1984;Muniruzzaman and Banks, 1989), many of which require restrictive assumptions about the geometry or the gravity field of the sources. Most often, forward modeling is the only way, absenting extensive sampling, to obtain an estimate of magnetization parameters which are, however, not unique.…”
Section: Introductionmentioning
confidence: 99%
“…He showed that once the equivalent source is obtained, the gravity field can be calculated at a regularly gridded horizontal plane. Emilia and Massey (1975) showed that for a 2D causative body, magnetization inclination can be estimated by solving the nonlinear inverse problem of a horizontal equivalent source layer with unknown magnetization distribution. Bhattacharyya and Chan (1977) and Bhattacharyya et al (1979) studied the reduction of gravity and magnetic data measured on an arbitrary surface of high topographic relief with equivalent source representation at observation points.…”
Section: Local Wavenumber Methodsmentioning
confidence: 99%
“…At the present there are only three commercially available airborne gravity gradiometry systems and some others are either under test or under constructions. These gradiometers have been developed to commercial systems based on the first gravity gradiometers developed by Lockheed Martin between 1975(Difrancesco, 2007; 1-The Air-FTG ® system: This is a full tensor gradiometry system which measures five independent GGT components, namely g xx , g xy , g xz , g yy , and g yz . The g zz component is calculated from Laplace's equation.…”
Section: Airborne Gravity Gradiometrymentioning
confidence: 99%